PENGGUNAAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR GEOGRAFI MATERI LITOSFER DI SMA NEGERI 1 KABILA BONE BOLANGO - Suci surahmi; Fitryane Lihawa; Daud Yusuf (JAMBURA GEO EDUCATION JOURNAL, 2021)
The Use of Animated Video Media in Improving Students'Learning Outcomes on Geography Subject of Lithosphere Topic: A Study Conducted in Senior High School, SMAN Kabila, Bone Bolango Regency. The objective of this classroomaction research is to improve students' learning outcomes by the application of animated video media on the subject of geography of the lithosphere topic; it was conducted in senior high school SMAN Kabila, Bone Bolango Regency. This study relied on the data of students' learning outcomes, which were from multiple-choice test. Further, as many as 33  this study comprised two cycles i.e., cycle I and II. According to the result of cycle 1, out of 33 students, 17 students met the standard score, while the remaining 16 ( 53,33% ) was the opposite. The percentage increased in cycle II, where 26 students ( 86,67% ) were able to meet the minimum standard, and only 23,33% were yet to satisfy the standard completion. All in all, the use of animated video media improves students' learning outcomes in the site area.